2020
DOI: 10.1093/nar/gkaa318
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin stimulated reversal of topoisomerase 2 DNA-protein crosslinks by TDP2

Abstract: Tyrosyl-DNA phosphodiesterase 2 (TDP2) reverses Topoisomerase 2 DNA–protein crosslinks (TOP2-DPCs) in a direct-reversal pathway licensed by ZATTZNF451 SUMO2 E3 ligase and SUMOylation of TOP2. TDP2 also binds ubiquitin (Ub), but how Ub regulates TDP2 functions is unknown. Here, we show that TDP2 co-purifies with K63 and K27 poly-Ubiquitinated cellular proteins independently of, and separately from SUMOylated TOP2 complexes. Poly-ubiquitin chains of ≥ Ub3 stimulate TDP2 catalytic activity in nuclear extracts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Polyubiquitin chains formed by K11 and K63 can also promote proteasomal targeting ( Bedford et al, 2011 ; Kravtsova-Ivantsiv and Ciechanover, 2012 ; Meyer and Rape, 2014 ; Saeki et al, 2009 ). In addition, K27 or K63 polyubiquitin chains may help in docking TDP2 to TOP3Bccs and stimulating TDP2 by engaging its UBA domain as it does for TOP2ccs ( Schellenberg et al, 2020 ). Overall, our results establish the importance of the ubiquitin-proteasomal pathway for the repair of TOP3Bccs in addition to its role for both TOP1ccs and TOP2ccs ( Sun et al, 2020b , 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyubiquitin chains formed by K11 and K63 can also promote proteasomal targeting ( Bedford et al, 2011 ; Kravtsova-Ivantsiv and Ciechanover, 2012 ; Meyer and Rape, 2014 ; Saeki et al, 2009 ). In addition, K27 or K63 polyubiquitin chains may help in docking TDP2 to TOP3Bccs and stimulating TDP2 by engaging its UBA domain as it does for TOP2ccs ( Schellenberg et al, 2020 ). Overall, our results establish the importance of the ubiquitin-proteasomal pathway for the repair of TOP3Bccs in addition to its role for both TOP1ccs and TOP2ccs ( Sun et al, 2020b , 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…While it was later shown that the TDP2 UBA domain binds K27-and K63-linked polyubiquitin chains, the TDP2 UBA does not bind ubiquitinated TOP2 and the ubiquitinated target required for TDP2dependent repair remains unknown. It is speculated that a ubiquitin-dependent interaction involving the TDP2 UBA domain may induce a conformational change in the TDP2 active site, or may mediate interactions with ubiquitinated histones at DNA damage sites (Kawale and Povirk, 2018;Rao et al, 2016;Schellenberg et al, 2020).…”
Section: Top2 Ubiquitinationmentioning
confidence: 99%
“…Recruitment of TDP2 potentially occurs via two different mechanisms depending on the mechanism used to process or remodel the TOP2 adduct. If TOP2 is marked with ubiquitination for subsequent proteasomal degradation, this could recruit TDP2 via it’s N-terminal ubiquitin binding (UBA) domain ( Rao et al, 2016 ; Schellenberg et al, 2020 ). Binding of ubiquitin to the UBA domain of TDP2 does stimulate its phosphodiesterase activity in vitro and TDP2 does bind to a pool of ubiquitinated proteins in vivo , but this pool of ubiquitinated proteins does not appear to include TOP2 ( Rao et al, 2016 ; Schellenberg et al, 2020 ).…”
Section: Repair Of Topoisomerase-mediated Dna Damagementioning
confidence: 99%
“…If TOP2 is marked with ubiquitination for subsequent proteasomal degradation, this could recruit TDP2 via it’s N-terminal ubiquitin binding (UBA) domain ( Rao et al, 2016 ; Schellenberg et al, 2020 ). Binding of ubiquitin to the UBA domain of TDP2 does stimulate its phosphodiesterase activity in vitro and TDP2 does bind to a pool of ubiquitinated proteins in vivo , but this pool of ubiquitinated proteins does not appear to include TOP2 ( Rao et al, 2016 ; Schellenberg et al, 2020 ). Still, there is conflicting evidence for whether deletion of the UBA domain confers hypersensitivity to etoposide depending on the cell-type used, suggesting potential cell-type specific roles for the UBA domain of TDP2 that may or may not be independent of its role in the recruitment of TDP2 to stalled TOP2ccs ( Rao et al, 2016 ; Schellenberg et al, 2020 ).…”
Section: Repair Of Topoisomerase-mediated Dna Damagementioning
confidence: 99%
See 1 more Smart Citation